What is the functional background of filigree extracellular matrix and cell-cell connections at the interface of the renal stem/progenitor cell niche? - Will W. Minuth; Lucia Denk (Hygeia Press di Corridori Marinella, 2015)
Development of a nephron is induced by a reciprocal exchange of morphogenetic proteins between epithelial and mesenchymal cells within the renal stem/progenitor cell niche. For sustaining concentration of diffusing proteins high, it is believed that an intimate contact exists between involved cells. However, actual morphological data show that both types of stem/progenitor cell bodies are separated by an interface. To analyze details of this arrangement, neonatal rabbit kidneys were fixed in traditional glutaraldehyde (GA) solution for transmission electron microscopy. For an enhanced contrast fixation of samples was performed in GA solution including either cupromeronic blue, ruthenium red or tannic acid. To record always the same perspective, embedded blocks of parenchyma were cut in orientated vertical and transverse planes to the lumen of lining collecting duct tubules. Screening of samples fixed by GA solution demonstrates a constant separation of stem/progenitor cell bodies by an unobstrusively looking interface. In contrast, improved fixation of specimens in GA solution including cupromeronic blue, ruthenium red or tannic acid unveils between them earlier not visible filigree extracellular matrix. Further projections of mesenchymal cells covered by this matrix cross the interface to contact epithelial cells. The end of a projection does not dangle but is mounted by a special plug connection. At this site the plasma membranes of mesenchymal and epithelial cells are connected via tunneling nanotubes. Regarding this unique arrangement the principal question is to what extent illustrated extracellular matrix and cell-cell connections are involved in the exchange of morphogenetic proteins during induction of a nephron.   Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano